Service Requirements of Liver Transplant Anesthesia Teams: Society for the Advancement of Transplant Anesthesia Recommendations. Issue 4 (10th March 2020) - Hendrickse, Adrian; Crouch, Cara; Sakai, Tetsuro; Stoll, William D.; McNulty, Monica; Pivalizza, Evan; Sridhar, Srikanth; Diaz, Geraldine; Sheiner, Patricia; Nevah Rubin, Moises I.; Al‐Khafaji, Ali; Pomposelli, James; et al.
Abstract : There are disparities in liver transplant anesthesia team (LTAT) care across the United States. However, no policies address essential resources for liver transplant anesthesia services similar to other specialists. In response, the Society for the Advancement of Transplant Anesthesia appointed a task force to develop national recommendations. The Conditions of Transplant Center Participation were adapted to anesthesia team care and used to develop Delphi statements. A Delphi panel was put together by enlisting 21 experts from the fields of liver transplant anesthesiology and surgery, hepatology, critical care, and transplant nursing. Each panelist rated their agreement with and the importance of 17 statements. Strong support for the necessity and importance of 13 final items were as follows: resources, including preprocedure anesthesia assessment, advanced monitoring, immediate availability of consultants, and the presence of a documented expert in liver transplant anesthesia credentialed at the site of practice; call coverage, including schedules to assure uninterrupted coverage and methods to communicate availability; and characteristics of the team, including membership criteria, credentials at the site of practice, and identification of who supervises patient care. Unstructured comments identified competing time obligations for anesthesia and transplant services as the principle reason that the remaining recommendations to attend integrative patient selection and quality review committees were reduced to a suggestion rather than being a requirement. This has important consequences because deficits in team integration cause higher failure rates in service quality, timeliness, and efficiency. Solutions are needed that remove the time‐related financial constraints of competing service requirements for anesthesiologists. In conclusion, using a modified Delphi technique, 13 recommendations for the structure of LTATs were agreed upon by a multidisciplinary group of experts.